Effect of resistance training on local muscle endurance in middle-aged and older adults: A systematic review with meta-analysis and meta-regression. (June 2023) - Wang, Boliang; Davies, Timothy B.; Way, Kimberley L.; Tran, Derek L.; Davis, Glen M.; Singh, Maria Fiatarone; Hackett, Daniel A.
Highlights: There is evidence of diminished local muscle endurance capabilities during dynamic contractions in older adults, which may negatively impact activities of daily living. This is the first systematic review and meta-analysis to investigate the effect of resistance training or acute resistance exercise exposure on local muscle endurance in middle-aged and older adults. Analyses showed that resistance training has a large positive effect on local muscle endurance, irrespective of volume or loading intensity. The optimum training paradigm for local muscle endurance has not been defined and further studies with direct comparisons of various training modalities are needed to refine the prescription. Abstract: Background: Local muscle endurance (LME) is a significant indicator of muscle health and function in middle-aged and older adults. However, resistance training (RT) practices which optimise performance in this population are currently unclear. This study examined: 1) the effect of RT on LME; and 2) the impact of acute resistance exercise program variables on LME in middle-aged and older adults. Methods: Five electronic databases were searched using terms related to RT, LME, and older adults. Random effects (Hedges' g) meta-analyses were undertaken to estimate the effect of RT on upper and lower body LME assessed via maximal repetitions during an isotonic test. The impact of resistance exercise program variables on LME effects was explored using meta-regression analyses. Results: Fifteen studies met the inclusion criteria for this review. Upon sensitivity analysis, one study was removed. Large effects favoured RT for LME of the upper body ( g = 1.10, p < 0.001) and lower body ( g = 1.18, p < 0.001). Large effects on LME from RT were found irrespective of training intensity or other resistance exercise program variables. Moderate heterogeneity and publication bias were found in most analyses. Discussion: RT is an effective means for improving LME in middle-aged and older adults. Optimal training characteristics have not been defined by this review, as improvement in LME was unrelated to RT volume or loading intensity. Caution is warranted when interpreting the findings due to heterogeneity and bias present in existing literature. Additional studies are needed with direct comparisons of various training techniques.